Percutaneous transforaminal approach for the diagnosis and treatment of a case of lumbar tuberculous spondylodiscitis with epidural abscess. - Lovatón-Espadín, Rolando (2022)
Pott’s disease or tuberculous spondylodiscitis accounts for less than 1% of tuberculosis cases. However, the indolent clinical course of this condition leads to a generally delayed diagnosis and to the destruction of the vertebral structures. The resulting spinal deformity requires surgical treatment, which is complex and demands a prolonged hospital stay. In this report, we present the case of a 52-year-old male patient who was diagnosed with lumbar spondylodiscitis by clinical and imaging studies, without response to an empiric antibiotic treatment. Transforaminal percutaneous approach, a minimally invasive technique, allowed the diagnosis of tuberculous spondylodiscitis and a symptomatic improvement of the patient.